The late-phase reaction after nasal airway challenge with allergen - Samoliński, Bolesław; Rapiejko, Piotr (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2010)
Mast cell derived mediators and cytokines are responsible for cellular recruitment and development of the late-phase response. Eosinophils are the major effector cells in the nasal secretions of patients with allergic rhinitis during the responses to allergen challenges. Nasal allergic symptoms are the result of the influence of mediators on neural, vascular and glandular structures of the nasal mucosa. The author describes reactions in the nasal mucosa in the early and late phase of the allergic reaction.